STUDI PARAMETRIK DAKTILITAS BALOK-KOLOM BAJA BERPENAMPANG I - Sudarsono, Atin
Abstract: This thesis presents parametric study of I-shaped steel beam-column ductility. The effects of beam-column slenderness, flange width-thickness ratio, magnitude of axial copression load and yield-strength are studied to investigate those influence on the ductility. For this purpose, nonlinear finite element program such as MSC/Nastran which accounts material nonlinearity and inelastic buckling is used to analyzed elastoplastic behavior of the beam-column. The results show that slenderness of beam-column and flange width-thickness ratio are the major factor affecting ductility. Yield-strength and magnitude of the compression axial load has a great influence on the ductility if the value of beam-column slenderness and flange width-thickness ratio are small. Based on the result of parametric study, empirical formulas are proposed to predict ductility.